ANALISIS SEKTOR BASIS DAN NON BASIS TANAMAN PANGAN SERTA KONTRIBUSI SEKTOR PERTANIAN TERHADAP PDRB DI PROVINSI PAPUA BARAT - Yolanda Maria Woyaa; Uria, Darmawanto; Saut Simanungkalit (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
The aims of this research is to determine the growth of the agricultural sector in West Papua Province, determine the contribution of the agricultural sector to GRDP in West Papua Province and determine the basic and non-basic sectors of food commodities in West Papua Province. Methods used in This research is a simple mathematical method. By using the growth formula to determine the development of the agricultural subsector, the contribution formula to see the contribution of the agricultural subsector to GRDP, and the Location Quotient (LQ) formula. The conclusions from the research on basic and non-based sectors of food crops and the contribution of agriculture are (1) The highest growth in the agricultural sector in West Papua Province in 2021 based on current prices of 10.46% and constant prices of 7.73%. And the lowest based on constant prices in 2022 and 2023 3.00%, 0.03% and current prices 0.02%. (2) The highest contribution from the agricultural sector in West Papua Province in 2023 is in the fisheries sub-sector based on constant prices at 5.39%, current prices at 5.74% and the lowest in the agricultural services sub-sector based on constant prices at 0.6% and the price applies 0.5%. (3) The leading commodity base for food crops in 2023, namely rice, is found in Fak-Fak Regency, Wondama Bay, Bintuni Bay, Manokwari and South Manokwari where LQ > 1, while corn as the leading commodity in 2021 is found in Manokwari, Sorong, Regency. Raja Ampat, Tambraw, Arfak Mountains and Sorong City